(untitled) (Economic and Political Thought, 2013)
The article aims to present guidelines on financial systems’ comparative analysis. The author focuses on the guidelines on the comparison of the size of financial institutions and financial markets in the analyzed countries, the level of accessibility of financial institutions and financial markets to a financial market member and the efficiency and stability of financial institutions and financial markets. The article presents a series of indicators useful in the conduction of a comparative analysis of the financial systems in different countries.